1980
DOI: 10.1143/jjap.19.l707
|View full text |Cite
|
Sign up to set email alerts
|

Long-Period Antiphase Domain Structures of Al-Ti Alloys near Composition Al3Ti

Abstract: Superstructures of Al-Ti alloys in the composition range from Al3Ti to Al2Ti were studied by electron diffraction. It was shown that the Al24Ti8 which has been reported to be a low temperature modification of the Al3Ti phase has a long-period one-dimensional antiphase domain structure (1d-APS) with average domain size M=8/6, where M is measured in unit cell length of the fundamental lattice. In addition, the 1d-APS's with M=1.60–1.91 were found in the specimens containing 26.5 to 32.5 at.% Ti and it was sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 1 publication
1
16
0
1
Order By: Relevance
“…According to the phase diagram proposed by Loiseau et al, [19] these long period structures are only stable above 1000 ЊC. Miida et al [34] reported one-dimensional antiphase domain structures for alloys containing 67.5 to 73.5 at. pct Al heat treated at 1200 ЊC.…”
Section: Discussionmentioning
confidence: 99%
“…According to the phase diagram proposed by Loiseau et al, [19] these long period structures are only stable above 1000 ЊC. Miida et al [34] reported one-dimensional antiphase domain structures for alloys containing 67.5 to 73.5 at. pct Al heat treated at 1200 ЊC.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of the phases TidAl. and TizAl5 in A13xTi~.~ alloys has also been reported as the result of other detailed electron microscope investigations [29,30,34] but these works have not provided an indication of the origins of these phases.…”
Section: Phase Equilibia Of the Ti-ai Systemmentioning
confidence: 97%
“…For the same composition range, Miida et al [27,34] and Loiseau et al [30,35], working primarily with electron diffraction, identified a series of ld-APS (long period structures), which were distinguished in terms of composition and structure by the average domain size M and the axial ratio c/a of the fundamental sub-cell of the structure. Miida et al [27] suggested that the ld-APS found in an alloy containing 31 at.% Ti, after quenching from 1473 K, had M=1.79 and corresponded to TisAln.…”
Section: Phase Equilibia Of the Ti-ai Systemmentioning
confidence: 99%
“…The I4/amd space group of the 0 phase is, however, the same as the TiAl 2 intermetallic compound [27,[60][61][62][63][64]. In the binary Ti-Al system, the TiAl 2 phase can take on two different crystal structures h-TiAl, and r-TiAl 2 depending on temperature [27] (see Figure 3.18).…”
Section: The 1100 900 and 700°c Isothermsmentioning
confidence: 99%